2007
DOI: 10.1007/s11709-007-0001-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of steel structures considering damage cumulation

Abstract: recognised fact that the stiffness, strength and energy dissipation capacity of structures deteriorate when subjected to cyclic loading. This deterioration is associated with the damage cumulating process in the material which already has micro-defects resulting from the construction and service period. The damage accumulated will inevitably affect the remaining strength or life of structures. Structural failure occurs when the damage has accumulated to a critical level. However, due to the complexity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…n semi-cycle, and the unloading process is approximately elastic. E D n is the elastic modulus with damage accumulation, which in respect of D n can be calculated by Equation (9) based on damage mechanics theory and Shen [30,31]. E 0 is the original elastic modulus, g and h are the damage parameters like η and ξ.…”
Section: A Model Of Hysteretic Curve With Damage Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…n semi-cycle, and the unloading process is approximately elastic. E D n is the elastic modulus with damage accumulation, which in respect of D n can be calculated by Equation (9) based on damage mechanics theory and Shen [30,31]. E 0 is the original elastic modulus, g and h are the damage parameters like η and ξ.…”
Section: A Model Of Hysteretic Curve With Damage Accumulationmentioning
confidence: 99%
“…It is critical to find a constitutive model that can be used to describe the cyclic characteristics of welding materials. Shen [30,31] put forward a hysteresis model of steel, which has been considered as the damage accumulation of steel under cyclic loads. The model has good applicability but did not consider the effect of nonlinear hardening.…”
Section: Introductionmentioning
confidence: 99%
“…Although the peak acceleration of Mexico earthquake record (1962) was only 0.105g, for its long duration, the damage around the station was serious. After studying the development of a reliable analytical model for seismic analysis of steel structures, Shen and Wu (2007) concluded that the damage cumulation effect was considerable and important in structural seismic analysis. Analyzing a suite of seven structural models with strength and stiffness degrading characteristics by a suite of almost 500 strong-motion accelerograms, Bommer et al (2004) believed that seismic performance evaluation method for masonry structure should be improved and take duration into account.…”
Section: Introductionmentioning
confidence: 99%
“…Kratzig [29] proposed HSE indicators for providing estimates of seismic vulnerability by extending the structural damage concepts of aging structures to seismic design, where structures fail by passing the damage evolution over an ultimate bound. Shen and Shen [30] established a practical hysteresis model of steel members that takes the effects of damage accumulation and fracture into consideration and includes the calculation of the HSE index, the effects of HSE on the yielding point, the modulus of elasticity and hardening coefficient of steel, the stressestrain hysteresis relationship and the fracture criterion. Dimova and Negro estimated the structural vulnerability by fragility analysis incorporating the numerical models of the structural response in different seismic intensity levels into the experimental data [31].…”
Section: Introductionmentioning
confidence: 99%